Difusi Inovasi Melalui Pendampingan Mgmp Matematika Smp Dalam Pembuatan Video Virtualisasi Manipulatif Konkret Untuk Pembelajaran Jarak Jauh - Isti Hidayah; A Agoestanto; A.N Cahyono; Z Abidin (Jurnal Pengabdian UntukMu NegeRI, 2021)
During the Covid-19 pandemic, teacher problems increased to maintain the effective implementation of mathematics learning. The available classical and individual concrete manipulative product innovations cannot be used in learning because learning policies during the pandemic still have to be carried out as distance learning. To overcome this problem, assistance was carried out in making videos of using concrete manipulatives to MGMP as concrete manipulative virtualization. The results of this activity show that there is an increase in the average score of the overall pre-self test competence to the post-self test. The same is true for each competency. In addition to producing video products on target, video quality is better, as well as increasing personal partners who act as actors and narrators. As a suggestion in this activity, mentoring continues to be carried out on an ongoing basis as a stage of diffusion of other innovation products and guidance for MGMP and partners of this activity can transmit to other MGMP member teachers.